Can smartphone be used to support learning? - I S Kurniawan; F S Tapilow; T Hidayat; W Setiawan (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Smartphone technology is growing very rapidly equipped with features that are increasingly sophisticated. Currently, almost all peoples have a smartphone as it can help us to get information in various forms. In education, a variety of information is required to support the learning process. However, can the smartphonebe used to support learning? This study aims to describe the use of smartphones among students. Using survey method, this study involved 133 prospective biology teachers. The results showed that the use of smartphones is for social media (32.14%), games (27.39%), music (32.06%) and learning (8.40%). These results indicated that the use of smartphones to support learning is the lowest compared with other purposes. Regarding these, most students argued that the limitations of the screen become a constraint using a smartphone to support the learning process. In the future, we must think how smartphones can be maximized to support learning.